PENERAPAN METODE GAUGING ABSENCE OF PREREQUISTES DALAM PROMOSI JABATAN KARYAWAN TETAP PADA PT ABC - Agustina, Andri (Universitas Bina Darma, 2014)
Motivations that drive people to participate actively in an organization include the opportunity to get ahead. Opportunity to advance in an organization called the promotion (raising position). A promotion also means removal from a position to another position that has a status and a higher responsibility. Job promotion is one part of the placement program conducted by the company. For the companies looking for employees who have no qualifications assessed in accordance with the needs of the new positions needed to be promoted. To analyze employees according to particular occupations performed by the method of profile matching, where in this process must first determine competence (skills) needed by an office. In the process of matching profile outline a process of comparing an individuals competency in job competency so as to know the difference competence (also called GAP).